What’s Going on Out There? An exploration of K–12 PE Curricular Models and Content Taught in Public Schools - Hodges, Michael; Laughlin, Michael; Brusseau, Timothy (The Physical Educator, 2018)
Little is known about which curricular models and activity units are being taught in public schools. This exploratory study examined the K–12 physical education (PE) content and curricular models being implemented. Supervisors of PE recruited from one northeastern state participated in a 25-item questionnaire. Descriptive statistics and frequencies were calculated. Sixty-nine of 92 questionnaires were usable and included in the data analysis. Findings suggest that few districts were using a curricular model at the elementary (K–5) level (27%). Another common response of adopted curricular models at the elementary level was Movement Education (17.6%). At the secondary level, No Model (35%) and Fitness Education (25.6%) were common responses. Specific units such as volleyball, basketball, and weight training yielded the highest responses, while field hockey, golf, archery, lacrosse, and tennis yielded the fewest responses. The findings suggest that K–12 PE curricula may not reflect current trends and mandates. The key determinants could be a lack of curricular model use and heavy reliance upon activities known to present challenges toward standards-based education (i.e., softball). Perhaps K–12 PE and PE preparation programs can connect to effectively articulate a curriculum, and adopt and train on curricular approaches aiming to increase teacher effectiveness and reach national standards.Subscribe to TPE
Number: 5
Keywords: Content; Curricular Models; PETE; Units; dept.hms

Assistive Technology: What Physical Educators Need to Know - Laughlin, Michael K., Nathan M., Murata, Michele, Gonnelli; Larranaga, John (Journal of Physical Education, Recreation & Dance, 2018)
Assistive technology supplements and supports the learning of students with disabilities in school and at home. Thanks to federal mandates, students with disabilities receive consideration for assistive technology devices and services — the tools and supports needed to achieve determined learning outcomes. Assistive technology devices and services operate as a process, ensuring students with disabilities receive optimal access to learning across all educational settings and subject areas. This article provides physical educators with a working knowledge of the assistive technology process along with recommendations for supporting their students with disabilities.
_eprint: https://doi.org/10.1080/07303084.2017.1417930
Keywords: dept.hms

Universal design for learning: Review and recommendations for EFL instruction - Timpe-Laughlin, Veronika; Laughlin, Michael K. (Inklusiver Englischunterricht. Impulse zur Unterrichtsentwicklung aus fachdidaktischer und sonderpädagogischer Perspektive, 2018)
Keywords: dept.hms

Development of a Scale Measuring Chinese Preservice Physical Education Teachers’ Beliefs About the Physical Education Profession - Fan, Yao; Keating, Xiaofen D.; Liu, Jingwen; Zhou, Ke; Shangguan, Rulan; Knipe, Robert (The Asia-Pacific Education Researcher, 2018)
This project aimed to develop a valid and reliable scale measuring Chinese preservice physical education teachers’ beliefs about the physical education profession (PPET-BPEP). The domains and items were created from a conceptual analysis of the previous literature and PPETs’ responses to an open-ended survey. Six experts in the field of physical education and educational psychology evaluated the content validity of the scale. The reliability and factorial validity of the scale were examined utilizing a sample of 696 Chinese PPETs. The PPET-BPEP scale with 12 items embedded in two domains revealed acceptable content validity, internal structure validity, and internal consistency. The two domains were labeled as “sense of calling” and “value of physical education profession” based on the shared content of items in each domain. We recommend using PPET-BPEP scale for PPET recruitment and preparation. The scale can also help establish teacher belief scales in other subject matters. Future validation of the scale is needed in different countries and institutions.
Keywords: Future physical education teacher; Professional beliefs; Survey development; Validity and reliability; dept.hms

The Effects of the VK Performance Insole on Running Economy in Highly-Trained Distance Runners: 518 Board# 1 May 30 1: 00 PM-3: 00 PM - Gregory, Robert W.; Lunn, William R.; Robertson, Marc I.; Axtell, Robert S. (Medicine & Science in Sports & Exercise, 2018)
Keywords: dept.hms

Gradual vs. Maximal Acceleration: Their Influence on the Prescription of Maximal Speed Sprinting in Team Sport Athletes. - Young, Warren B; Duthie, Grant M; James, Lachlan P; Talpey, Scott W; Benton, Dean T; Kilfoyle, Anthony (Sports, 2018)
The primary purpose of this study was to determine if a difference existed between peak speed attained when performing a sprint with maximal acceleration versus from a gradual build-up. Additionally, this investigation sought to compare the actual peak speed achieved when instructed to reach 75% and 90% of maximum speed. Field sport athletes (n = 21) performed sprints over 60 m under the experimental conditions, and the peak speed was assessed with a radar gun. The gradual build-up to maximum speed (8.30 +/- 0.40 m.s-1) produced the greater peak speed (effect size = 0.3, small) than the maximum acceleration run (8.18 +/- 0.40 m.s-1), and the majority of participants (62%) followed this pattern. For the sub-maximum runs, the actual mean percentage of maximum speed reached was 78 +/- 6% for the 75% prescribed run and 89 +/- 5% for the 90% prescription. The errors in attaining the prescribed peak speeds were large (~15%) for certain individuals, especially for the 75% trial. Sprint training for maximum speed should be performed with a gradual build-up of speed rather than a maximum acceleration. For sub-maximum interval training, the ability to attain the prescribed target peak speed can be challenging for field sport athletes, and therefore where possible, feedback on peak speeds reached should be provided after each repetition.
4 citations (Crossref) [2023-10-31] Place: Switzerland Young, Warren B. School of Health and Life Sciences, Federation University, Ballarat 3350, Australia. w.young@federation.edu.au. Duthie, Grant M. School of Exercise Science, Australian Catholic University, North Sydney 2060, Australia. grant.duthie@acu.edu.au. James, Lachlan P. School of Health and Life Sciences, Federation University, Ballarat 3350, Australia. l.james@latrobe.edu.au. James, Lachlan P. Department of Rehabilitation, Nutrition and Sport, School of Allied Health, La Trobe University, Melbourne 3086, Australia. l.james@latrobe.edu.au. Talpey, Scott W. School of Health and Life Sciences, Federation University, Ballarat 3350, Australia. talpeys1@southernct.edu. Talpey, Scott W. Exercise Science Department, Southern Connecticut State University, New Haven, CT 06515, USA. talpeys1@southernct.edu. Benton, Dean T. Atletico, Melbourne, Australia. dbenton@atletico.com.au. Kilfoyle, Anthony. School of Health and Life Sciences, Federation University, Ballarat 3350, Australia. tonykilfoyle@hotmail.com.
Keywords: Acceleration; Conditioning; Programming; Team sport; dept.hms; peer-reviewed

Flourishing and academic engagement among adolescents with overweight and obesity - Rupp, Kristie; McCoy, Stephanie M. (International Journal of Adolescent Medicine and Health, 2018)
Abstract Background Overweight and obesity in adolescence are associated with several negative health indicators; the association with flourishing, an indicator of overall well-being, is less clear. Objectives To examine associations between weight status and indicators of flourishing and academic engagement in adolescents. Subjects Analyses included 22,078 adolescents (10–17 years) from the 2016 National Survey of Children’s Health. Methods Adolescents were grouped according to body mass index (BMI) classification; outcomes included indicators of flourishing and academic engagement. Logistic regression models assessed the odds of each outcome comparing adolescents with overweight and adolescents with obesity to healthy weight adolescents. Results For flourishing, adolescents with overweight and adolescents with obesity were less likely to stay calm during a challenge (17% and 30%, respectively; p < 0.01); adolescents with obesity were 30% less likely to finish a task they started (p < 0.001), and 34% less likely to show interest in new things (p < 0.001) in comparison to healthy weight peers. Adolescents with obesity were 26% less likely to care about doing well in school (p < 0.001), and adolescents with overweight and adolescents with obesity were significantly less likely to complete all required homework (19% and 34%, respectively) (p < 0.001), in comparison to healthy weight peers. Conclusions A comprehensive approach to addressing overweight and obesity in adolescence should target improving academic engagement and flourishing to promote overall well-being.
3 citations (Crossref) [2023-10-31]
Keywords: academics; adolescence; dept.hms; dept.pch; flourishing; obesity; peer-reviewed

The effects of a carbon fiber shoe insole on athletic performance in collegiate athletes - Gregory, Robert W.; Axtell, Robert S.; Robertson, Marc I.; Lunn, William R. (Journal of Sports Science, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

Evaluating accelerometry thresholds for detecting changes in levels of moderate physical activity and resulting major mobility disability - Rejeski, W. Jack; Walkup, Michael P.; Fielding, Roger A.; King, Abby C.; Manini, Todd M.; Marsh, Anthony P.; McDermott, Mary McGrae; Miller, Emily Y; Newman, Anne B.; Tudor-Locke, Catrine; Axtell, Robert S.; Miller, Michael E. (Journals of Gerontology Series A-biological Sciences and Medical Sciences, 2018)
Background: An important decision with accelerometry is the threshold in counts per minute (CPM) used to define moderate to vigorous physical activity (MVPA). We explore the ability of different thresholds to track changes in MVPA due to a physical activity (PA) intervention among older adults with compromised function: 760 CPM, 1,041 CPM, and an individualized threshold. We also evaluate the ability of change in accelerometry and self-reported PA to attenuate treatment effects on major mobility disability (MMD). Methods: Data from a week of hip worn accelerometers and self-reported PA data (30-day recall) were examined from baseline, 6-, 12-, and 24-months of follow-up on 1,528 older adults. Participants were randomized to either PA or Health Education (HE). MMD was objectively defined by loss of ability to walk 400 m during the follow-up. Results: The three thresholds yielded similar and higher levels of MVPA for PA than HE (p ¡ .001), however, this difference was significantly attenuated in participants with lower levels of physical function. Self-reported PA that captured both walking and strength training totally attenuated the intervention effect for MMD, an 18% reduction to a 3% increase. Accelerometer CPMs showed less attenuation of the intervention effect. Conclusions: Accelerometry assessment within the LIFE study was not sensitive to change in level in physical activity for older adults with very low levels of physical function. A combination of self-report and objective measures are recommended for use in physical activity intervention studies of the elderly; limitations of accelerometry deserve closer attention.
6 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000430696300014 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Accelerometry; Aged; Aged; 80 and over; Female; Geriatric Assessment; Humans; LIFE-study; Male; Mobility Disability; Mobility Limitation; Motor Activity; Older Adults; Thresholds; Walking; accelerometry; aged; clinical trial; controlled study; dept.hms; female; geriatric assessment; human; male; motor activity; multicenter study; peer-reviewed; physiology; procedures; randomized controlled trial; very elderly; walking; walking difficulty

Rating of perceived exertion is a stable and appropriate measure of workload in judo. - Bromley, Sally J; Drew, Michael K; McIntosh, Andrew; Talpey, Scott (Journal of Science and Medicine in Sport, 2018)
OBJECTIVES: Heart rate (HR), blood lactate concentration [La] and/or rating of perceived exertion (RPE) have been utilised to monitor judo training load in technical and randori (competition training) sessions, but are yet to be investigated in mixed sessions containing both elements. Therefore the purpose of this study was to: (1) determine the stability of these variables, and (2) to assess the efficacy of RPE as a load variable for mixed judo sessions., DESIGN: Cross-sectional study., METHODS: Twenty-nine athletes attended two mixed training sessions at an international training camp. Bout and session characteristics, including RPE, physical and mental effort, heart rate (HR) and post-session [La] were recorded. A two-way random-effects intra-class correlation assessed variable stability. Multilevel mixed-effects ordered logistic regression investigated relationships between RPE and other variables for bouts and sessions., RESULTS: Average and minimum HR across sessions correlated highly (ICC=0.95 and 0.94, respectively). Good correlations existed between [La], session-RPE and mental effort, and fair correlation of max HR and physical effort. No relationships existed between [La]/HR and session-RPE. A unit increase in bout-RPE resulted in a 2.09 unit increase in physical, or a 1.36 unit increase in mental, effort holding all other bout variables constant. Gender and competitive level did not influence statistical models., CONCLUSIONS: Results provide further evidence that RPE can be used across a range of competitive levels and genders to monitor workload of mixed sessions and individual randori in judo. Physical effort may play a larger role than mental effort when athletes reflect on exertion during training. Copyright © 2018. Published by Elsevier Ltd.
4 citations (Crossref) [2023-10-31] Place: Australia Bromley, Sally J. Australian Institute of Sport, Australia; Australian Centre for Research into Injury in Sport and its Prevention (ACRISP), Federation University Australia, Australia. Electronic address: sally.bromley@ausport.gov.au. Drew, Michael K. Australian Institute of Sport, Australia; Australian Centre for Research into Injury in Sport and its Prevention (ACRISP), Federation University Australia, Australia. McIntosh, Andrew. Australian Centre for Research into Injury in Sport and its Prevention (ACRISP), Federation University Australia, Australia. Talpey, Scott. Australian Centre for Research into Injury in Sport and its Prevention (ACRISP), Federation University Australia, Australia; Exercise Science Department, Southern Connecticut State University, United States.
Keywords: *Martial Arts/ph [Physiology]; *Physical Exertion; *Workload; Adolescent; Adult; Athletes; Athletic performance; Combat sport; Cross-Sectional Studies; Epidemiological monitoring; Female; Heart Rate; Humans; Judo; Lactic Acid; Lactic Acid/bl [Blood]; Male; Martial Arts; Martial arts; Physical Exertion; Training load; Workload; Young Adult; adolescent; adult; article; athlete; athletic performance; blood; comparative effectiveness; cross-sectional study; dept.hms; drug efficacy; epidemiological monitoring; exercise; female; gender; heart rate; human; human experiment; human tissue; judo; lactic acid; male; martial art; peer-reviewed; physiology; workload; young adult

Muscle strength assessment - Axtell, Robert S. (ACSM's Exercise Testing and Prescription, 2018)
ACSM’S Exercise Testing and Prescription adapts and expands upon the assessment and exercise prescription-related content from ACSM’s Resource Manual for Guidelines for Exercise Testing and Prescription, 7th Edition, to create a true classroom resource. Fully aligned with the latest edition of ACSM’s flagship title, ACSM’s Guidelines for Exercise Testing and Prescription , this practical resource walks students through the process of selecting and administering fitness assessments, using Guidelines to interpret results, and drafting an exercise prescription that is in line with Guidelines parameters .Designed for today’s learners, the text is written in a clear, concise style, and enriched by visuals that promote student engagement. As an American College of Sports Medicine publication, the book offers the unsurpassed quality and excellence that has become synonymous with titles by the leading exercise science organization in the world.The nuances of fitness assessment and the particulars of crafting exercise prescriptions are explored in expansive sections throughout the book.A full section devoted to Special Populations prepares students to meet the needs of the full range of both typically healthy and special needs clients they’ll see in practice.Comprehensive case studies written by experts to reinforce practical applications of concepts.A wide range of online resources includes laboratory materials and activities that provide opportunities for hands-on learning, and a library of journal articles that helps students connect research to practice.100% alignment with the most up-to-date version of the ACSM’s Guidelines for Exercise Testing and Prescription enhances the learning experience, making it easy to go back and forth between Guidelines and the text.eBook available. Fast, smart, and convenient, today’s eBooks can transform learning. These interactive, fully searchable tools offer 24/7 access on multiple devices, the ability to highlight and share notes, and much more.
Keywords: dept.hms

Special considerations for the lifespan: Elderly population - Robertson, M.I.; Axtell, Robert (ACSM's Exercise Testing and Prescription, 2018)
ACSM’S Exercise Testing and Prescription adapts and expands upon the assessment and exercise prescription-related content from ACSM’s Resource Manual for Guidelines for Exercise Testing and Prescription, 7th Edition, to create a true classroom resource. Fully aligned with the latest edition of ACSM’s flagship title, ACSM’s Guidelines for Exercise Testing and Prescription , this practical resource walks students through the process of selecting and administering fitness assessments, using Guidelines to interpret results, and drafting an exercise prescription that is in line with Guidelines parameters .Designed for today’s learners, the text is written in a clear, concise style, and enriched by visuals that promote student engagement. As an American College of Sports Medicine publication, the book offers the unsurpassed quality and excellence that has become synonymous with titles by the leading exercise science organization in the world.The nuances of fitness assessment and the particulars of crafting exercise prescriptions are explored in expansive sections throughout the book.A full section devoted to Special Populations prepares students to meet the needs of the full range of both typically healthy and special needs clients they’ll see in practice.Comprehensive case studies written by experts to reinforce practical applications of concepts.A wide range of online resources includes laboratory materials and activities that provide opportunities for hands-on learning, and a library of journal articles that helps students connect research to practice.100% alignment with the most up-to-date version of the ACSM’s Guidelines for Exercise Testing and Prescription enhances the learning experience, making it easy to go back and forth between Guidelines and the text.eBook available. Fast, smart, and convenient, today’s eBooks can transform learning. These interactive, fully searchable tools offer 24/7 access on multiple devices, the ability to highlight and share notes, and much more.
Keywords: dept.hms

Effect of age on dynamic walking balance in a healthy population between the ages of 20 and 80 years - Robertson, Marc; Gregory, Robert (Physical Therapy and Rehabilitation, 2018)
2 citations (Crossref) [2023-10-31] Citation Key Alias: robertsonEffectAgeDynamic2018a
Keywords: dept.hms; peer-reviewed

Solving the acoustic issue in physical education settings - Ryan, Stu; Swartz, Daniel R (International Journal of Physical Education, Fitness and Sports, 2018)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/079-502-562-751-84X tex.type: [object Object]
Keywords: dept.hms; peer-reviewed

Bright 1 bodies: extending the bright bodies family-based intensive lifestyles therapy to adolescents with type 1 diabetes - Ash, Garrett I; Joiner, Kevin L; Savoye, Mary; Baker, Julien S; Gerosa, James; Kleck, Emma; Patel, Neha S; Stultskolehmainen, Matthew A; Weinzimer, Stuart A; Grey, Margaret (Annals of Behavioral Medicine, 2018)
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/134-102-073-475-880 tex.type: [object Object]
Keywords: dept.hms; peer-reviewed

Safety and health outcomes of a physical activity program for adolescents with Type 1 Diabetes - Ash, Garrett I; Joiner, Kevin L; Savoye, Mary; Baker, Julien S; Gerosa, James; Kleck, Emma; Patel, Neha S; Stultskolehmainen, Matthew A; Weinzimer, Stuart A; Grey, Margaret (ACSM's 65th Annual Meeting, 2018)
Citation Key Alias: lens.org/149-915-175-995-302
Keywords: dept.hms; ⛔ No DOI found

The status of physical activity opportunities in Idaho schools. - Berei, Catherine P; Karp, Grace Goc; Kauffman, Katie (The Physical Educator, 2018)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/104-344-030-444-113 tex.type: [object Object]
Keywords: dept.hms